2017
DOI: 10.3141/2609-10
|View full text |Cite
|
Sign up to set email alerts
|

From the Last Mile to the Last 800 ft

Abstract: Pickup and delivery operations are an essential part of urban goods movements. However, rapid urban growth, increasing demand, and higher customer expectations have amplified the challenges of urban freight movement. In recent years, the industry has emphasized improving last-mile operations with the intent of focusing on what has been described as the last leg of the supply chain. In this paper, it is suggested that solving urban freight challenges requires an even more granular scale than the last mile, that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…This review finds that some authors focus solely on deliveries of parcels, while others address other types of deliveries, such as groceries [79,125,130,151,163] and spare parts [11,73]. To achieve a more unified and comprehensive view, there is a need to embrace all types of deliveries in last mile logistics, both forward and reverse flow [71,114,141]. However, the review shows that reverse logistics are not yet widely included in the literature as an integrated part of last mile logistics.…”
Section: Define the Scope Of Last Mile Logisticsmentioning
confidence: 99%
“…This review finds that some authors focus solely on deliveries of parcels, while others address other types of deliveries, such as groceries [79,125,130,151,163] and spare parts [11,73]. To achieve a more unified and comprehensive view, there is a need to embrace all types of deliveries in last mile logistics, both forward and reverse flow [71,114,141]. However, the review shows that reverse logistics are not yet widely included in the literature as an integrated part of last mile logistics.…”
Section: Define the Scope Of Last Mile Logisticsmentioning
confidence: 99%
“…Acceptable time for searching for parking among private vehicle drivers for shopping trips was found to be between 8 and 13 mins (Chaniotakis & Pel, 2015). It can be expected that the tolerance for commercial drivers is much lower (Butrina, Del Carmen Girón-Valderrama, Machado-León, Goodchild, & Ayyalasomayajula, 2017), and search-for-parking could contribute to the "stress from time pressure" among commercial drivers, which has been mentioned as the second most important safety-critical issue (Hanowski, Wierwille, & Dingus, 2003). Finally, while varying electricity prices is much discussed in the charging context (mostly in connection with smart charging to level the energy grid demands), it is found that it plays only a minor role in the decision-making of passenger EV drivers, both for the location and schedule choice (Philipsen et al, 2018;Speidel & Bräunl, 2014).…”
Section: Charging Servicesmentioning
confidence: 99%
“…There is little guarantee that a charging location will be available for the driver, unless it is exclusive for loading and unloading activities (Morganti & Browne, 2018). However, in case the locations cannot be reserved, such as for on-street parking, parking search strategies may be used (Butrina et al, 2017).…”
Section: Opportunity Charging Strategymentioning
confidence: 99%
“…However, the literature on last mile freight does not differentiate between the operational activities and challenges of freight carriers across the whole metropolitan area and inside the inner-city area. Butrina et al suggest that there is limited knowledge of the delivery practices of freight carriers in the last hundreds of metres [13]. Businesses require deliveries directly to their stores.…”
Section: Introductionmentioning
confidence: 99%